Strategies to Strengthen the Role of Women in Sustainable Waste Management: a SWOT Study in the Village of Daleman Kidul - Yenny Reiza Fitriana; Asti Purwanti; Sekar Putri Denisa; Nur Amalia Hidayah; Dian Marlina Verawati (ICON Publisher, 2025)
Waste management in Indonesia has become a pressing environmental issue due to population growth and urbanization. With around 250 million people, Indonesia is the fourth most populous country and the second largest contributor of plastic waste in the world. By 2024, an estimated 19.5 million tons of waste is generated annually, yet only 46.1% is properly managed. Effective management is important to achieve the Sustainable Development Goals (SDGs), particularly responsible consumption and production. Community-based waste management (CBWM) that empowers women is a solution to waste reduction. This research optimizes the role of women in sustainable waste management through a case study of the Nawasena Kemala Digital Waste House in Daleman Kidul Village. A descriptive qualitative method with in-depth interviews, observation, and data triangulation was used. Results showed that women play a central role in collecting, sorting, and processing waste into economically valuable products, but face obstacles such as lack of incentives, training, and community awareness. SWOT analysis revealed strengths of women's active role and community innovation, weaknesses of limited training and facilities, opportunities of policy support and incentives, and threats of lack of participation and funding. Policy implications emphasize the need for incentives, certification training, and gender integration for sustainable waste management at the local level.